Rheology and processing of polymer nanocomposites - Thomas, Sabu; Muller, René, 1955-; Abraham, Jiji (John Wiley & Sons, Inc., 2016)
Rheology and Processing of Polymer Nanocomposites examines the current state of the art and new challenges in the characterization of nanofiller/polymer interactions, nanofiller dispersion, distribution, filler-filler interactions and interfaces in polymer nanocomposites. A one-stop reference resource for important research accomplishments in this area, it benefits academics, researchers, scientists, and engineers in the field of polymer nanocomposites in their daily work.